Brazilian political theater movements: from the 1960s to confrontations with neoliberalism (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
The research articulates two moments of Brazilian political theater: the rise of epic theater in conjunction with the popular struggles of the 1960s and, with the impact of the 1964 coup and the dictatorship, the subsequent regressive position of theater in the country's cultural system while television rose as a means of information and entertainment. The second moment addresses the period after the dictatorship, the struggle of group theater workers in resistance to neoliberalism, and since the beginning of the 21st century, articulating experiences of social movements, theater collectives and university groups. The case study addresses the experiences of collective Terra em Cena articulated with the network that makes it up.
Keywords: political theater; social movements; epic theater; Nuestra America Network